Implementation of Zakat Mal Law in the Islamic Political Economic System - Tatha Amelia Fretika; Lailatul Fitria; M Firdaus Tri Kuncoro; Mashudi (Al-Iffah: Journal of Islamic Sciences Research, 2025)
Implementation of zakat mal law in the Islamic economic system is an effort to realize social and economic justice. Zakat mal is an obligation for Muslims who have certain wealth, and its collection and distribution are regulated by sharia principles. In the context of Islamic economics, zakat mal plays a role as an instrument to reduce economic disparities, overcome poverty, and strengthen social solidarity. The process of implementing zakat mal involves zakat institutions that are responsible for collecting and distributing the zakat. Transparency and accountability are key in running this system, by ensuring that zakat funds are distributed in accordance with sharia provisions to support the welfare of the community. In addition, the government has a role in creating regulations that support the practice of zakat mal, providing incentives for companies and individuals who contribute significantly. Implementation of zakat mal law also requires education for the community so that understanding of the importance of zakat as an integral part of the Islamic economic system increases. Thus, zakat mal can be an effective instrument to achieve the goals of Islamic economics, namely justice, balance, and the welfare of the community as a whole.